Effect of cryopreservation on sperm DNA fragmentation and apoptosis rates in the testicular tissue of domestic cats - Macente, B. I.; Apparicio, M. [UNESP]; Mansano, C. F.M.; Tavares, M. R. [UNESP]; Fonseca-Alves, C. E. [UNESP]; Sousa, B. P.; Bertolo, P. H.L. [UNESP]; Vasconcelos, R. O. [UNESP]; Teixeira, E. S.; Toniollo, G. H. [UNESP] (Elsevier, 2019)
The objectives of the present study were to evaluate the damage caused by cryopreservation on sperm DNA and estimate the percentage of cell apoptosis in tissue after thawing. Testicles of cats were sectioned into of 0.3 cm3 and 0.5 cm3 fragments and evaluated for DNA damage using acridine orange and semi-quantitatively through histo-morphological and immunohistochemical methods (caspase-3). Other fragments were placed in cryotubes with diluent containing either 3% glycerol or 3% propanediol, and were cryopreserved. Evaluation using acridine orange indicated there was a difference with use of propanediol and glycerol on DNA damage in 0.5 cm3fragments, with the latter being more effective than the former for cryopreservation. Results from histomorphological evaluations indicated there was a greater cell integrity among germ cells that were not cryopreserved, based on criteria assessed (detachment of cells from basal membrane, retraction of seminiferous tubule epithelium, visibility of the spermatogonia nucleoli and nuclear spermatogonia condensation), for both sizes of fragments. The values for these variables decreased after cryopreservation, with there being no differences as a result of size of fragment stored or between cryoprotectants used (P > 0.05). The staining for caspase-3 differed for the cytoplasm, nuclei and germ cells. Assessment of these staining patterns indicated the fresh fragments had an amount of cell damage and there was a similar amount of damage detected in cryopreserved fragments. This finding indicated that there was considerable efficacy in preserving the tissue fragments with use of the freezing protocols that were evaluated in this study.
Keywords: Acridine orange; Biotechnology; Felines; Immunohistochemistry; Reproduction